2015
DOI: 10.1097/aud.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and Patient Satisfaction Among 19 Patients Who Received Implants Intended for Hybrid Hearing

Abstract: Objectives:To measure patient satisfaction and correlate to hearing results in partially deaf patients, after hearing preservation cochlear implant surgery with hybrid hearing strategy, and to evaluate the stability of residual low-frequency hearing (LFH) over time.Design:A patient satisfaction survey and a retrospective, 2-year follow-up journal study. Nineteen partially deaf patients intended for hybrid hearing responded to a questionnaire when they had used their cochlear implants for at least a year. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A study that attempted to assess this same issue via a quality of life questionnaire found no significant differences in the quality of life of bilaterally deaf children with a CI and contralateral hearing aid versus bilaterally deaf children with bilateral hearing aids and normal-hearing children ( Perez-Mora et al, 2012 ). Studies investigating long-term patient satisfaction with CI through young adulthood and beyond found similar results as many patients reported that the benefits of CI outweighed any potential loss of residual hearing or other negative side effects ( Galvin et al, 2014 ; Erixon and Rask-Andersen, 2015 ).…”
Section: Patient Satisfactionmentioning
confidence: 69%
“…A study that attempted to assess this same issue via a quality of life questionnaire found no significant differences in the quality of life of bilaterally deaf children with a CI and contralateral hearing aid versus bilaterally deaf children with bilateral hearing aids and normal-hearing children ( Perez-Mora et al, 2012 ). Studies investigating long-term patient satisfaction with CI through young adulthood and beyond found similar results as many patients reported that the benefits of CI outweighed any potential loss of residual hearing or other negative side effects ( Galvin et al, 2014 ; Erixon and Rask-Andersen, 2015 ).…”
Section: Patient Satisfactionmentioning
confidence: 69%
“…The use of electroacoustic stimulation and hybrid CIs is becoming increasingly common, with rates of hearing preservation rising concordantly in recent years as the use of these devices become more popular (15). Electroacoustic stimulation has been show to lead to higher patient satisfaction and gains in speech understanding even in the face of loss of some residual hearing (16). Its use expands the eligible pool of hearing-impaired subjects who could benefit from insertion of a CI.…”
Section: Discussionmentioning
confidence: 99%
“…Erixon et al in the Ear and Hearing, which has one of the highest Impact Factor journals in this field, have written in 2015: "Skarzynski et al (2012) called the first group electrical complement patients and the second group electro-acoustic stimulation patients" [28]. Von Ilberg with an international group of collaborators in a multicenter study published in the Audiology and Neurotology in 2011 [19] has mentioned: "The most expanded indication for electro-acoustic stimulation (EAS) has been reported by the Warsaw group, who implanted candidates with markedly better acoustic hearing in the frequencies between 125 and 500 Hz.…”
Section: Discussionmentioning
confidence: 99%